THU0625 CAN WE IMPROVE INPATIENT REFERRALS TO RHEUMATOLOGY IN A TEACHING HOSPITAL IN THE UK?. (June 2019) - Vivekanantham, Arani; Mateen, Zenab Sarwar; Wheatley, Roseanna; Myers, Rachael; Watson, Pippa; Little, Jayne
Abstract : Background: Inpatient referrals to rheumatology vary nationally from paper/electronic methods to phone conversations with the rheumatology registrar. In our Trust, which includes two large teaching hospitals in the UK, rheumatology referrals were hand written, faxed to secretaries and then given to the rheumatology registrar. This method was time consuming and referrals often lacked vital information. The referrer would also not know when the registrar had received the referral. A quality improvement project (QIP) in another UK hospital has shown an electronic referral system to be more efficient and safer for patients [1]. Objectives: This QIP aimed to evaluate the current system for inpatient referrals to two rheumatology departments within one large UK NHS trust and to identify aspects for improvement. Methods: Two hundred and ten inpatient rheumatology referrals received between January 2018 - January 2019 were analysed retrospectively for inclusion of important information such as, patient location and referrer's contact details. Results: The review of current referrals identified several areas for improvement. The results are summarised in Table 1 . The reasons for referrals ranged from swollen, painful joints to new rashes and medication reviews. A process mapping session was undertaken to identify how the referral system could be improved. An electronic referral system, via the local electronic patient record (EPR), was created. As well as ensuring that there is an audit trail and referrals are received in a timely manner, referrers are provided with a proforma to direct them to supply the relevant information. There is also functionality for the rheumatology team to reply to the referral with advice, which creates a new permanent document in the patient's EPR. The Orthopaedic team, who are the first point of call for hot joints in our Trust, were consulted to ensure that there were not any unintended consequences as a result of this change. The form included the following sentence to avoid delays in patient care for septic arthritis: 'patients with suspected septic arthritis should be referred to Orthopaedics by ringing the on-call registrar'. Conclusion: The current method of paper rheumatology referrals was inefficient and referrals often lacked vital information. The new electronic system will ensure relevant items are included in the referral and that there is a clear audit trail of the referral process. Referrals will be re-evaluated again in three months to assess the impact of this change on outcomes including time to rheumatology review and inpatient bed stay. In the second round of this project we plan to include an education component onto the rheumatology referral form. For example, if gout is suspected, the referrer will be linked to guidelines and patient information sheets to assist best management whilst awaiting review. We would encourage others to consider their referral systems- could you improve yours? References: [1] Shephard E, Stockdale C, May F, et al. E-referrals: improving the routine interspecialty inpatient referral system. BMJ Open Quality 2018;7:e000249. doi:10.1136/bmjoq-2017-000249 Disclosure of Interests: None declared